2009
DOI: 10.1111/j.1600-0463.2009.02518.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6, but not IL‐4, stimulates chemokinesis and TNF stimulates chemotaxis of tissue mast cells: involvement of both mitogen‐activated protein kinases and phosphatidylinositol 3‐kinase signalling pathways

Abstract: An increase in the number of mast cells within tissues is observed in many pathophysiological conditions. Current data indicate that migration of mature mast cells might be one of the key mechanisms responsible for rapid local accumulation of these cells. Considering that interleukin (IL)-6 and IL-4, as well as tumour necrosis factor (TNF), influence mast cell activity in various ways, the purpose of the current study was to examine whether these cytokines function as rat peritoneal mast cell chemoattractants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The ability of basophils to independently recruit eosinophils and neutrophils in chronic allergic inflammation was demonstrated in a mouse model, and the low abundance (<2%) of basophils in the infiltrates suggested that basophils initiate rather than effect chronic inflammation [33]. In addition, mast cells have the ability to secrete serotonin, enzymes like chymase and tryptase, peptides, growth factors, cytokines, and chemokines, which act as powerful chemoattractants, regulate migration of mast cells, and activate platelets, among many other effects [34–37]. Important cytokines produced by both mast cells and basophils include thymic stromal lymphopoetin (TSLP), IL-4, IL-5, IL-13, IL-25, and granulocyte/macrophage colony stimulating factor (GM-CSF) [3842].…”
Section: Role Of Il-18 In Allergic Diseasementioning
confidence: 99%
“…The ability of basophils to independently recruit eosinophils and neutrophils in chronic allergic inflammation was demonstrated in a mouse model, and the low abundance (<2%) of basophils in the infiltrates suggested that basophils initiate rather than effect chronic inflammation [33]. In addition, mast cells have the ability to secrete serotonin, enzymes like chymase and tryptase, peptides, growth factors, cytokines, and chemokines, which act as powerful chemoattractants, regulate migration of mast cells, and activate platelets, among many other effects [34–37]. Important cytokines produced by both mast cells and basophils include thymic stromal lymphopoetin (TSLP), IL-4, IL-5, IL-13, IL-25, and granulocyte/macrophage colony stimulating factor (GM-CSF) [3842].…”
Section: Role Of Il-18 In Allergic Diseasementioning
confidence: 99%
“…1, 2 These include the clinical observations that IL-6 levels relate to the severity of disease in systemic mastocytosis 3, 4 acute 5 and chronic urticaria, 6 and asthma. 7 In vitro, IL-6 promotes HuMC maturation, 8 adhesion to extracellular matrix, 9 chemokinesis, 10 and survival, the latter through IgE dependent production of mast cell derived IL-6. 11 IL-6 is also routinely used to supplement stem cell factor (SCF) to generate HuMCs from cord or peripheral blood progenitor (CD34 + ) cells.…”
Section: Introductionmentioning
confidence: 99%
“…(30) In addition, TNF-α is known as a target cytokine in therapy of allergic disease, inflammatory, and immune disease because the mast cell is the only known cell to prestore TNF-α and is able to release this mediator immediately upon activation. (31,32) In current study, M-tang treatment induced significantly the inhibitory effect on the PMA plus A23187-induced secretion and expression of TNF-α. These data also indicate that M-tang has the effective anti-inflammatory as a result of its reduction of TNF-α production in mast cells.…”
Section: Discussionmentioning
confidence: 89%